Curcumin alleviates LPS-induced inflammation and oxidative stress in mouse microglial BV2 cells by targeting miR-137-3p/NeuroD1. Issue 66 (25th November 2019) - Gao, Feng; Lei, Jing; Zhang, Zhaowei; Yang, Yanling; You, Haojun
Abstract : Curcumin has been reported to exert protective effects on inflammation-related diseases, including spinal cord injury (SCI). Abstract : Curcumin has been reported to exert protective effects on inflammation-related diseases, including spinal cord injury (SCI). Numerous evidence have suggested miRNAs are one of the important targets for curcumin during its anti-inflammatory function. However, little is known about the contribution of miRNAs on the role of curcumin in SCI. Thus, the objective of this study is to determine the role of miRNA (miR)-137-3p during curcumin treatment after SCI. Expression of miR-137-3p and NeuroD1 was detected using RT-qPCR and western blot assay. Inflammation and oxidative stress were measured with the protein expression levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and inducible nitric oxide synthase (iNOS). The target binding between miR-137-3p and NeuroD1 was confirmed via the luciferase reporter assay and RNA immunoprecipitation. LPS induced a higher expression of TNF-α, IL-1β, and iNOS in mouse microglia BV2 cells, which was attenuated by curcumin. miR-137-3p was downregulated and NeuroD1 was upregulated under LPS challenge. Curcumin also alleviated LPS-induced regulation on miR-137-3p and NeuroD1. The knockdown of miR-137-3p and ectopic expression of NeuroD1 could individually abolish the curcumin-mediated downregulation of TNF-α, IL-1β, and iNOS in LPS-challenged BV2 cells. Besides, NeuroD1 was inversely regulated by miR-137-3p via direct binding. Silencing of NeuroD1 reversed the miR-137-3p downregulation-mediated promoting effect on inflammation and oxidative stress in the presence of LPS and curcumin. Downregulation of miR-137-3p abolishes curcumin-mediated protection on LPS-induced inflammation and oxidative stress in mouse microglial BV2 cells depending on the direct upregulation of NeuroD1.